2020
DOI: 10.1136/bmjopen-2019-029818
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with positive user experience with primary healthcare providers in Mexico: a multilevel modelling approach using national cross-sectional data

Abstract: ObjectiveThis study aimed to investigate factors associated with patient experience with primary care in a large public health system in Mexico and determine the amount of variability in experience attributable to facility-level and state-level factors.MethodsWe analysed cross-sectional 2016 national satisfaction survey data from the Mexican Social Security Institute (IMSS). Patient-level data were merged with facility-level data and information on poverty by state. We assessed general contextual effects and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Correlation analyses between domains of patient experience and patients' overall rating of care allow for identifying priority interventions for improving the overall experience of care. The latest correlation analysis done by the Centers for Medicare & Medicaid Services (CMS) demonstrated that, similar to studies performed in China and Canada, communication and respect from nurses and doctors were best associated with high overall patient experience ratings (6,810). These results seem to transcend boundaries and types of care, as studies done in Mexico and the USA, within primary care or post-operative surgical care, attained similar results (9,11).…”
Section: Literature Reviewmentioning
confidence: 82%
See 1 more Smart Citation
“…Correlation analyses between domains of patient experience and patients' overall rating of care allow for identifying priority interventions for improving the overall experience of care. The latest correlation analysis done by the Centers for Medicare & Medicaid Services (CMS) demonstrated that, similar to studies performed in China and Canada, communication and respect from nurses and doctors were best associated with high overall patient experience ratings (6,810). These results seem to transcend boundaries and types of care, as studies done in Mexico and the USA, within primary care or post-operative surgical care, attained similar results (9,11).…”
Section: Literature Reviewmentioning
confidence: 82%
“…The latest correlation analysis done by the Centers for Medicare & Medicaid Services (CMS) demonstrated that, similar to studies performed in China and Canada, communication and respect from nurses and doctors were best associated with high overall patient experience ratings (6,810). These results seem to transcend boundaries and types of care, as studies done in Mexico and the USA, within primary care or post-operative surgical care, attained similar results (9,11). The World Health Organization (WHO), through a study measuring the relative importance of non-clinical aspects of care, demonstrated that across regions, population surveys emphasized the importance of prompt attention (access to care), dignity, and communication as part of the medical care they receive (12).…”
Section: Literature Reviewmentioning
confidence: 82%
“…In Uruguay, the high level of RC perceived at both care levels may be attributable to the smaller size of the study areas, which were located in smaller urban zones, and to the co-location of PC and SC doctors in the same health centres. These characteristics encourage doctors to get to know their patients [ 26 , 39 ], strengthening trust and mutual understanding, and creating a sense of responsibility in professionals towards their patients [ 3 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the Latin American studies available, some of which are comparative between countries [ 8 , 21 , 22 , 23 ], come mainly from Brazil [ 8 , 22 , 23 , 24 ], Mexico [ 21 , 22 , 25 , 26 ], and Colombia [ 8 , 21 , 22 , 23 , 27 ]. Likewise, very few of these study RC in a comprehensive way, with the majority focusing on analysing just one attribute of RC in PC—the consistency of the doctor [ 22 ], the doctor–patient bond [ 24 , 25 ], or communication with the doctor [ 27 ]—through either qualitative methods [ 27 ] or surveys of health services users [ 8 , 21 , 22 , 23 , 24 , 25 ] or people with social security in general [ 26 ]. Quantitative studies on chronic patients and SC doctors RC are extremely limited to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation